ASSESSING THE PAY OF TRAINING OF PHYSICAL EDUCATION FRONT OF YOUR DAY JOB (Fiep Bulletin - online, 2013)
The study aims to assess the remuneration of Professional Fitness front of his journey from working in most areas of focus discussed in the market today, Private and Public Schools, Higher Education Institution and Private Academies. Thus we believe the business is helping in the search for a better area of action in respect of professional achievement and an average value of remunerção that it deems appropriate to their journey to work. Searches were conducted with 58 practitioners from the above in Rio de Janeiro, capital of more than a year of training. Data were collected through a form with nine questions, which allowed the analysis of frequency, then the = 0.05). Among thesignificance was investigated by the chi-square ( results was noted that with regard to pay, approximately 82.14% to take as unfair. Thinking about leaving the profession 38.60%. They have to pay as the main reason for abandoning the profession 68.20%. The professional believes that the company realizes the so devalued and one of the factors that contribute most to this fact in his view is the lack of knowledge by the occupation. Most professional education is to the completion of Sensu Lato and it is this group, the post-graduates, including the strictest sense, it is possible to achieve better wages between 6 to 7 SM. The worst place to-day relationship work and pay are the academies and place of work are better relationship with the Private Higher Education Institutions. Through these results we could compare these areas and their indicators thereby confirming the expectations of common sense.
Keywords: Compensation; Labor Day; Business Areas